2007
DOI: 10.1021/jp067025q
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Alkanethiolate-Protected Gold Clusters with Unprecedented Core Sizes in the Thiolation of Polymer-Stabilized Gold Clusters

Abstract: Octadecanethiolate-protected gold (Au:SC18) clusters were prepared by the reaction of C18SH and Au clusters stabilized by poly(N-vinyl-2-pyrrolidone) (PVP). Four samples were fractionated by recycling size exclusion chromatography of the as-prepared Au:SC18 clusters, and their core sizes were determined to be 8, 11, 21, and 26 kDa by using laser desorption ionization mass spectrometry. Unexpectedly, the sequence of these core sizes is different from that (8, 14, 22, and 29 kDa) obtained by conventional reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 55 publications
8
107
0
Order By: Relevance
“…In the initial stages of the research, laser desorption ionization (LDI) was frequently used for this purpose. 15,16,21,32,33,3538 However, this provided only an approximated estimate of the core mass of Au:SR because the LDI process breaks CS bonds and probably AuAu bonds, resulting in the formation of fragments with the formula Au n S m . We utilized two methods to suppress fragmentation: electrospray ionization (ESI) 2228,30,3949 and matrix-assisted LDI (MALDI).…”
Section: Size Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stages of the research, laser desorption ionization (LDI) was frequently used for this purpose. 15,16,21,32,33,3538 However, this provided only an approximated estimate of the core mass of Au:SR because the LDI process breaks CS bonds and probably AuAu bonds, resulting in the formation of fragments with the formula Au n S m . We utilized two methods to suppress fragmentation: electrospray ionization (ESI) 2228,30,3949 and matrix-assisted LDI (MALDI).…”
Section: Size Selectionmentioning
confidence: 99%
“…Size focusing of preformed Au:SR clusters by thiol etching is currently the general approach for size-selective synthesis of magic Au:SR clusters. 33,44,5156 By using this approach and ESI mass spectrometry, we revealed that Au:SC n clusters with core masses of 8 and 29 kDa are ubiquitous magic clusters and that they can be formulated as Au 38 (SC n ) 24 and Au 144 (SC n ) 59 , respectively ( Figure 4). 43 Murray and Jin later reassigned the latter clusters as Au 144 (SC n ) 60 60 .…”
Section: Size Selectionmentioning
confidence: 99%
“…The synthesis of the positively charged AuNPs was based on the method of Tsunoyama et al [55,63]. Briefly, an aqueous solution of hydrogen tetrachloroaurate (III) (HAuCl 4 , 1 mM, 50 ml) was mixed with two different stabilizers, i.e., PVP (K-10, 10 kDa) and DMAP.…”
Section: Synthesis Of Aunpsmentioning
confidence: 99%
“…[1][2][3][4][5] The synthesis has reached the stage where clusters with a defined structural formula of Au(RS) can be routinely isolated. [6][7][8][9][10][11][12][13][14] These advances in synthesis and purification lead to the recent breakthrough in the crystal structure determination of the cluster. 15 It revealed that the monolayer is far from simple involving Au-thiolate oligomers that form a shell around the Au core in a "divide and protect motif".…”
Section: Introductionmentioning
confidence: 99%